Breaking the unvirtuous cycle: barriers and opportunities for research and development in Paraguay. A case study - Donna, María Lucila Gonzalez; León, María Luisa Cabañas; Colas, Cinthia Gauna; Gunsett, Alicia Pomata; Maniero, Silvia Ferreira; Osuna, David Olivares; Klimovsky, Ezequiel; Coradini, Lucas; Enrico, Diego; Chacón, Matías; Waisberg, Federico (Frontiers in Medicine, 2023)
Coordinated efforts are needed to break an unvirtuous cycle consolidated by low budget allocation for research and development, an insufficient number of clinical investigators and publications, and scarce private investment. There is an increasing interest in enhancing health research in Paraguay, materialized in the creation of specific programs that encourage the collaborative work of healthcare providers, basic scientists, and private investors. Nonetheless, a comprehensive approach is needed also to strengthen regulatory agencies and attract external sponsorship. While modern and currently popular topics, including artificial intelligence, real-world data, and translational research may represent key opportunities to seek investment, special policies should be adopted to prioritize research on the determinants of health in the Paraguayan population.This case study involved two main components: A literature review to analyze the regulatory framework, and the characteristics of past and ongoing research projects, and a semistructured survey to identify barriers and facilitators to promote clinical investigation in Paraguay.